2014
DOI: 10.1111/ecog.01027
|View full text |Cite
|
Sign up to set email alerts
|

Complex organism–environment feedbacks buffer species diversity against habitat fragmentation

Abstract: Understanding the factors that determine the extent of biodiversity loss following habitat destruction is central to ecosystem conservation and management. One potential factor is the ecological feedbacks between organisms and local environmental conditions, which can influence how species affect one another and, consequently, whether or not species persist in fragmented landscapes. We investigated this possibility using a spatially explicit individual‐based model of plant communities. In this model, plant spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Plant-soil feedbacks have been widely studied (Van der Putten et al 2013); however, their role in the context of habitat fragmentation and ecosystem degradation is still poorly understood (Zee and Fukami 2014). In a previous study (Pizano et al 2014), we showed that plant growth and survival was differentially impacted both in the greenhouse and the field by whole-soil microbial communities from habitats representing a disturbance gradient in a highly fragmented landscape.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Plant-soil feedbacks have been widely studied (Van der Putten et al 2013); however, their role in the context of habitat fragmentation and ecosystem degradation is still poorly understood (Zee and Fukami 2014). In a previous study (Pizano et al 2014), we showed that plant growth and survival was differentially impacted both in the greenhouse and the field by whole-soil microbial communities from habitats representing a disturbance gradient in a highly fragmented landscape.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, feedbacks mediated by soil organisms such as bacteria and non-AMF fungi in addition to AMF, may be crucial for decreasing the likelihood of species extinctions in fragmented landscapes by reducing the spatial clustering of individuals across the landscape (Zee and Fukami 2014), although further studies are required for exploring the diversity and ecological function of these organisms. Pastures accumulate AMF and non-AMF organisms that are detrimental to the grass B. brizantha, but benefit coffee and pioneer forest species, while forest fragments hold non-AMF, beneficial microbes that improved the growth of coffee.…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first major theme, diversity and assembly, was examined in all six contributions (Kissling and Schleuning , Melian et al , Michalet et al , Sandel , Schleuning et al , Zee and Fukami ). The primary conclusions associated with this theme included the following (but see Table for complete listings).…”
Section: Brief Overviewmentioning
confidence: 99%
“…Ecological networks – both trophic and non‐trophic – have been previously proposed as important to community assembly (Bascompte et al , Memmott et al , Verdú and Valiente‐Banuet , Kéfi et al ). In this special issue, three studies directly examined and discussed the importance of networks (Kissling and Schleuning , Melian et al , Schleuning et al ), whilst two others indirectly examined networks by exploring basal facilitation and interactions but did not explicitly invoke the term to describe their respective networks (Michalet et al , Zee and Fukami ). Consequently, the use of network tools to study biodiversity on environmental gradients and across scales is likely to continue to become an important future direction.…”
Section: Brief Overviewmentioning
confidence: 99%